Inclusion in the Dimensions of Personality - Hryhoriy Vasianovych; Olena Budnyk (Vasyl Stefanyk Precarpathian National University, 2022)
The article substantiates and offers a personalized approach to the analysis of the problem of inclusion. It emphasizes the need to adhere to the principle of human and child-centeredness in the process of working with people with special needs. It provides not only a humane, democratic attitude to a person, but also gives the opportunity to take full advantage of psychological and pedagogical influences on the spiritual development of the individual. An important element of this process is the active use of various ways and forms of mutual understanding, based on charity, empathy (methodology of Hermeneutics and Phenomenology). For factual analysis and presentation of the outlined problem, the real life of prominent domestic and foreign personalities with serious health problems (hearing loss - Ludwig van Beethoven, Maria Bashkirtseva, blindness - Homer, Democritus, Louis Braille, paralysis and cancer - Stephen Hawking, Kvitoslava Tsisyk, Yuri Titov), but showed  great will power, the desire for self-realization by means of creativity in the field of music, poetry, fine arts was used. These personalities set an example to follow in an inclusive educational institution.